A Pseudoaneurysm of the Deep Palmar Arch After Penetrating Trauma to the Hand: Successful Exclusion by Ultrasound Guided Percutaneous Thrombin Injection. (2016) - Bosman, A.; Veger, H.T.C.; Doornink, F.; Hedeman Joosten, P.P.A.
Abstract : Introduction: Pseudoaneurysm of the hand is a rare condition; most are treated surgically. Ultrasound guided thrombin injection has not previously been reported as a treatment option for pseudoaneurysms of the deep palmar arch. Report: A man was referred to the emergency department with a swollen, painful hand after penetrating trauma. On physical examination, a pulsating tumor was found on the dorsum of the hand. Imaging revealed a pseudoaneurysm vascularized by the deep palmar arch. Ultrasound guided percutaneous thrombin injection was successfully performed. Conclusion: Thrombin injection might be a safe alternative option in the treatment of pseudoaneurysm of the deep palmar arch. Highlights: Pseudoaneurysms of the deep palmar arch are infrequently diagnosed or described in literature. Current medical literature describes surgery as the preferred treatment option. US-guided percutaneous thrombin injection is a safe alternative option in the treatment of deep palmar arch pseudoaneurysms.